Direct Epitaxial Synthesis of Selective Two-Dimensional Lateral Heterostructures - Lee, Juwon; Pak, Sangyeon; Lee, Young-Woo; Park, Youngsin; Jang, A-Rang; Hong, John; Cho, Yuljae; Hou, Bo; Lee, Sanghyo; Jeong, Hu Young; Shin, Hyeon Suk; Morris, Stephen M; et al. (ACS nano, 2019)
Two-dimensional (2D) heterostructured or alloyed monolayers composed of transition metal dichalcogenides (TMDCs) have recently emerged as promising materials with great potential for atomically thin electronic applications. However, fabrication of such artificial TMDC heterostructures with a sharp interface and a large crystal size still remains a challenge because of the difficulty in controlling various growth parameters simultaneously during the growth process. Here, a facile synthetic protocol designed for the production of the lateral TMDC heterostructured and alloyed monolayers is presented. A chemical vapor deposition approach combined with solution-processed precursor deposition makes it possible to accurately control the sequential introduction time and the supersaturation levels of the vaporized precursors and thus reliably and exclusively produces selective and heterogeneous epitaxial growth of TMDC monolayer crystals. In addition, TMDC core/shell heterostructured (MoS2/alloy, alloy/WS2) or alloyed (Mo1–x W x S2) monolayers are also easily obtained with precisely controlled growth parameters, such as sulfur introduction timing and growth temperature. These results represent a significant step toward the development of various 2D materials with interesting properties.